Literature and sense of place in UK landscape strategy. (18th August 2019) - Edwards, Jess
ABSTRACT: The European Landscape Convention treats public perception and participation as essential to the integration of landscape within policy-making. Yet critiques of the implementation of the Convention in the UK through expert-led landscape character assessment (LCA) suggest that incorporation of public perception has been minimal and that the democratic potential of the Convention remains largely unrealised. This article examines the problematic role of perception in LCA and looks at examples where literature has been used to achieve a limited accommodation between subjective and objective modes of landscape characterisation. It argues for an expansion of this approach in the interests of public engagement, discussing landscape projects where participants have been supported to produce their own creative writing to cultivate not just landscape 'literacy' but a sense of connection with and stewardship of places.